Postural stability disorders—early signs of aging—in physically non-active prisoners - Piotr Łapiński; Aleksandra Truszczyńska-Baszak; Justyna Drzał-Grabiec; Adam Tarnowski (PeerJ, 2022)
Background There is a need for a study of possible relationship between serving a prison sentence and developing postural stability dysfunction. The aim of the study was to analyze postural stability of physically inactive prisoners. The study group consisted of 24 male prisoners aged 34.6 ± 7.02 years, imprisoned in closed prison and 30 healthy, non-active physically, aged 36.9 ± 7.5 years, who consisted control group. The subjects were imprisoned for a mean of 105.43 ± 58.48 months. Methods The static balance test was conducted on bi-modular stabilometric platform CQStab2P. Results We found statistically significant differences in several stability parameters. Prisoners results were significantly worse in parameters measured with eyes open: MA (mean amplitude p < 0.01), MAAP (mean amplitude in anterio–posterior plane p < 0.03), MAML (mean amplitude in medio—lateral plane p < 0.04), MaxAP (maximal sway in AP p < 0.01), MaxML (p < 0.01). With eyes closed the prisoner’s results were significantly worse in SPML (sway path in medio-lateral plane p = 0.01), better in MAML (p < 0.01) and MaxML (p < 0.01), and faster in MVML (mean velocity in medio-lateral plane p < 0.01). Conclusions (1) Diagnostics aimed at early diagnoses of ageing symptoms should be performed in prisons. It would allow for better prisoner management in terms of assessment of ability to work, free time activity offer and falls prevention. (2) In prisons, in addition to counteracting the typical causes of balance disorders, action should be taken to counteract the causes for balance disorders typical for prison environment, inter alia: sensory deprivation—by implementing programmes comprehensively activating prisoners, and hypokinesis—by implementing physical activity programmes that cater for the needs of older prisoners.